X-ray luminescent material as well as synthesis method and application thereof

By using supramolecular assembly technology of manganese metal and crown ether in an acid-free environment, the thermal stability and environmental pollution problems of crown ether metal halides during the synthesis of acidic environments are solved, and efficient and safe X-ray luminescent materials are achieved. Synthesis, providing a new acid-free synthesis pathway, reduces costs and improves safety.

CN119285682AActive Publication Date: 2025-01-10FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411179390.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2025-01-10
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

The existing crown ether metal halide X-ray luminescent materials are synthesized in acidic environments, resulting in poor thermal stability, large safety hazards, serious environmental pollution and high costs.

Method used

Using manganese metal as a complex, the organic-inorganic hybrid metal halide X-ray luminescent materials of crown ethers are synthesized through supramolecular assembly technology in an acid-free environment, and the complexation reaction between crown ether and alkaline earth metal is achieved efficiently. Safe and easy synthesis process.

Benefits of technology

It realizes efficient synthesis of X-ray luminescent materials, improves the thermal stability and safety of the materials, reduces production costs, reduces environmental pollution, provides a new acid-free synthesis path, and provides possibilities for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285682A_ABST
    Figure CN119285682A_ABST
Patent Text Reader

Abstract

The invention discloses an X-ray luminescent material as well as a synthesis method and application thereof, and belongs to the technical field of luminescent materials. The X-ray luminescent material is a crystal material, and the chemical formula of the X-ray luminescent material is Ca (at) LRMnCl4. 2H2O, wherein LR is a crown ether ligand. The X-ray luminescent material adopts a novel, rapid, simple and convenient supramolecular assembly technology, efficient synthesis of the X-ray luminescent material is realized, and the technology obviously shortens the synthesis period, simplifies the operation steps and reduces the synthesis danger by optimizing intermolecular interaction and an assembly path, selecting specific metal manganese and adopting an acid-free green synthesis path.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an X-ray luminescent material and a synthesis method and application thereof, belonging to the technical field of luminescent materials. Background Art

[0002] In recent years, X-ray detection and imaging technology, with its excellent performance and broad application prospects, has occupied an important position in many key fields such as medical diagnosis, environmental monitoring, defense industry flaw detection technology, nuclear technology and radiation safety detection, and even astronomical observation. This trend has prompted researchers around the world to explore and attach great importance to it. In this technology system, scintillator materials, as core components, have the ability to convert radiation energy into visible light. In addition to traditional scintillators, metal halide perovskite materials are also used in X-ray detection and imaging due to their strong X-ray absorption ability and high photoluminescence quantum yield (PLQY). Compared with the use of traditional small cations, crown ethers and alkali metal or alkaline earth metal ions form cationic complexes through host-guest interactions, which can be used as cationic building blocks to form low-dimensional organic-inorganic hybrid metal halide crystalline materials with metal halides. Its special low-dimensional structural characteristics bring higher structural stability and photoluminescence quantum efficiency. Its predictable low-dimensional structure provides a basis for the construction of a new supramolecular component library. The existing technology of X-ray based on crown ether metal halide that has been published so far is that cuprous is synthesized in an acidic environment. However, the thermal stability of cuprous complexes is poor, which has certain limitations on their practical application. At the same time, the acidic environment greatly increases the cost, safety, and environmental pollution issues. Specifically, the hazards brought by the acidic environment include the following aspects: 1. Corrosiveness and danger: Equipment corrosion: Acids are corrosive to reaction equipment and containers, which may cause equipment damage, shortened life, and even cause safety problems such as leakage. Operational danger: Many acids are highly corrosive, irritating or toxic, posing a threat to the health of operators. During the synthesis process, if improperly handled, it may cause accidents such as skin burns, eye injuries or inhalation of toxic gases; 2. Environmental pollution: Waste liquid treatment: The acidic waste liquid generated during the synthesis process is difficult to treat. If it is directly discharged into the environment, it will cause pollution to water bodies, soil and ecosystems. Gas emissions: Some metal halides may decompose and produce toxic gases such as hydrogen chloride under acidic conditions. The emission of these gases not only harms human health, but may also pollute the atmospheric environment; 3. Increased costs: Process costs: It is necessary to select corrosion-resistant materials to manufacture reaction equipment and take corresponding anti-corrosion measures. At the same time, the subsequent waste liquid needs to be treated separately, and additional procedures are added; 4. Time cost: Increased pre-treatment and post-treatment. Summary of the invention

[0003] In order to solve the problems that the poor thermal stability of the complexes existing in the prior art of crown ether metal halide crystalline materials has certain limitations on their practical applications, and the acidic environment used in the preparation process greatly increases the cost, safety and environmental pollution, the present application provides an X-ray luminescent material and a synthesis method and application thereof, adopts a new type of fast and simple supramolecular assembly technology to achieve efficient synthesis of X-ray luminescent materials, and uses manganese metal as a complex to realize the synthesis process in an acid-free environment.

[0004] This application adopts the following technical solutions:

[0005] According to one aspect of the present application, an X-ray luminescent material is provided, wherein the X-ray luminescent material is a crystalline material, and the chemical formula is Ca@L R MnCl4·2H2O;

[0006] Among them, L R It is a crown ether ligand.

[0007] Optionally, the crown ether ligand is selected from at least one of the supramolecular entities of the macrocyclic structure represented by formula (1) to formula (12):

[0008]

[0009] The flexible designability of the macrocyclic host is reflected in the exquisite control of the host size, the diverse selection of peripheral groups, and the clever introduction of asymmetric substituents. These design strategies enable the macrocyclic host to accurately match the alkaline earth metal, thus realizing the synthesis of organic-inorganic hybrid manganese-based halide X-ray luminescent materials based on crown ethers for the first time.

[0010] Crown ethers, as the best molecular building blocks, show excellent selectivity in complexing metal ions and organic cations, providing us with a powerful tool for precisely controlling supramolecular structures. This selectivity not only ensures the accuracy and predictability of the assembly process, but also greatly enriches the diversity of the final products, highlighting the great potential of crown ethers in supramolecular chemistry.

[0011] According to another aspect of the present application, a method for preparing the above-mentioned X-ray luminescent material is provided, comprising the following steps:

[0012] S1. obtaining a crown ether ligand;

[0013] S2. Dissolving a mixture of crown ether ligands, calcium chloride and manganese chloride in alcohol, and obtaining the X-ray luminescent material after the solvent evaporates.

[0014] Previous reports on crown ether organic-inorganic hybrid materials have mostly focused on copper-based halides, and usually require assembly in an acidic environment. However, in this application, we innovatively adopted a strategy of replacing the copper-based with the manganese-based, and successfully achieved the assembly process in an acid-free environment. This transformation not only simplifies the synthesis steps and reduces production costs, but also reduces the safety and environmental risks brought by the acidic environment, making industrial production possible.

[0015] Optionally, in step S2, the molar ratio of the crown ether ligand, calcium chloride, and manganese chloride is 1:(1-2):(1-2);

[0016] Optionally, the usage ratio of the crown ether ligand to the alcohol is 1 mmol:4-10 mL.

[0017] Optionally, in step S2, the conditions for the solvent to volatilize include: a temperature of 20 to 40° C. and a volatilization time of 10 to 30 minutes.

[0018] Optionally, in step S2, the alcohol is selected from at least one of ethanol and methanol.

[0019] Optionally, in step S1, the method for preparing the crown ether ligand comprises:

[0020] A mixture containing the starting material, p-toluenesulfonate raw material and sodium hydroxide is dissolved in 1,4-dioxane, refluxed, filtered and concentrated to obtain a crude product;

[0021] The crude product was extracted with chloroform / saturated brine to obtain the crown ether ligand.

[0022] Optionally, the starting material is selected from at least one of (2R,2R)-2,3-butanediol and R-1,1-bi-2-naphthol.

[0023] Optionally, the p-toluenesulfonate-based raw material is selected from at least one of triethylene glycol di-p-toluenesulfonate and pentylene glycol di-p-toluenesulfonate.

[0024] Optionally, the molar ratio of the starting material, the p-toluenesulfonate raw material, and the sodium hydroxide is 1:(0.5-1.5):(2-3);

[0025] Optionally, the usage ratio of the starting material to 1,4-dioxane is 1 mmol:4-8 mL.

[0026] Optionally, the conditions of the reflux reaction include: a reaction temperature of 90 to 110° C. and a reaction time of 48 to 72 h.

[0027] According to another aspect of the present application, there is also provided an application of the above X-ray luminescent material or the X-ray luminescent material prepared according to the above method in X-ray detection and imaging technology.

[0028] The beneficial effects of this application include:

[0029] (1) The X-ray luminescent material provided in the present application is a low-dimensional organic-inorganic hybrid metal halide crystalline material formed by the interaction between the cation module constructed by crown ether and the metal manganese halide anion, through a supramolecular assembly strategy regulated by fine intermolecular forces, which combines the flexibility of organic components and the stability of inorganic components.

[0030] (2) The synthesis process of the X-ray luminescent material provided by the present application does not require the use of acid, improves safety and production, conforms to the concept of green chemistry and sustainable development, and completely breaks the limitation that the synthesis of traditional crown ether crystal materials must rely on an acidic environment, creates a new acid-free synthesis path, and successfully achieves the rapid, simple, and efficient synthesis of X-ray luminescent materials. The synthesis process utilizes the high designability of organic ligands and the unique properties of manganese groups, especially the complexation of crown ethers with alkaline earth metals as cationic modules. This innovative design greatly simplifies the synthesis process, reduces the potential dangers in the synthesis process, improves the efficiency and safety of the synthesis, and also provides new ideas for the synthesis of 0D hybrid manganese-based halides with specific optical properties.

[0031] (3) This application has achieved the first successful application of crown ether organic-inorganic hybrid manganese-based halides in the field of X-ray luminescence. The X-ray luminescent material provided in this application, as a scintillator of the core component, can efficiently convert X-rays into visible light signals, providing more accurate and rapid image information for medical diagnosis, safety inspection, scientific research and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 For this application, ligand L R Self-assembly process and assembled Ca@L R Schematic diagram of the single crystal structure of MnCl4·2H2O.

[0033] Figure 2 For this application Ca@L R PXRD and simulated XRD of MnCl4·2H2O crystalline materials.

[0034] Figure 3 For this application Ca@L R Properties of MnCl4·2H2O crystal materials: (a) is the thermogravimetric analysis curve; (b) is the solid UV-visible diffuse reflectance spectrum; (c) is the excitation / emission spectrum; (d) is the fluorescence decay curve of the single crystal.

[0035] Figure 4 For this application Ca@L R Emission spectrum (PL) and radioluminescence spectrum (RL) of MnCl4·2H2O crystal material. DETAILED DESCRIPTION

[0036] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0037] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0038] They were used without further purification. Deuterated solvents were purchased from Adamas and J&K Technologies.

[0039] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0040] One-dimensional NMR spectra were measured by a Bruker Biospin Avance III (400MHz) NMR analyzer from Germany. The chemical shift values ​​of hydrogen spectra were determined based on the residual peak of deuterated solvents. Powder X-ray diffraction was tested by a tabletop X-ray analyzer from Japan Rigaku Corporation. The single crystal structure was tested by a single crystal diffractometer-Synergy-R-Mo from Japan Rigaku Corporation. Optical spectra were tested by an FS5 spectrometer in Edinburgh, UK. Thermogravimetry was tested by a comprehensive thermal analysis test from Nanjing Huicheng Instrument Co., Ltd.

[0041] Example 1

[0042] Step 1: Obtain ligand L R

[0043] As shown in the reaction process diagram of formula (1), (2R, 2R)-2,3-butanediol (7.6 g, 84 mmol), triethylene glycol di-p-toluenesulfonate (37 g, 89 mmol) and sodium hydroxide (9 g, 225 mmol) were dissolved in 500 ml of 1,4-dioxane. The mixture was refluxed at 101°C for three days. The reaction mixture was filtered and concentrated under reduced pressure. The crude product was further purified by chloroform / saturated brine extraction to obtain a yellow oily product, which is the ligand L shown in formula (1). R (Yield: 32%, 4.5 g, 14.06 mmol).

[0044] The results of nuclear magnetic resonance testing are 1H NMR (400MHz, CD3CN, 298K) δ = 3.80-3.71 (m, 4H), 3.59-3.65 (m, 4H), 3.54-3.58 (m, 4H), 3.46-3.50 (m, 4H), 3.39-3.45 (m, 4H), 1.18 (d, J = 6.2Hz, 12H).

[0045] Step 2: Ca@L R Synthesis of MnCl4·2H2O Crystal Materials

[0046] like Figure 1 As shown in the reaction process diagram, at room temperature, the ligand L prepared in Example 1 R (0.5 g, 1.56 mmol), calcium chloride (0.173 g, 1.56 mmol) and manganese chloride (0.196 g, 1.56 mmol) were dissolved in 10 mL of ethanol. After the solvent evaporated at room temperature, green block crystals were obtained in 15 minutes, which was Ca@L R MnCl4·2H2O crystal material (yield: 75%, based on manganese chloride). Crystal structure diagram as shown Figure 1 As shown, PXRD and simulated XRD are as follows Figure 2 shown.

[0047] Example 2

[0048] Steps 1 and 2 of the crystal material synthesis are the same as those in Example 1, except that the ligand L is obtained. R The raw materials in the process are: (2R,2R)-2,3-butanediol is replaced by the same molar amount of R-1,1-bi-2-naphthol, triethylene glycol di-p-toluenesulfonate is replaced by the same molar amount of di-p-toluenesulfonic acid pentylene glycol, and the ligand L is prepared. R It is a crystalline material having a structure shown in formula (2).

[0049]

[0050] Test Example 1: Ca@L R Optical Testing of MnCl4·2H2O Crystal Materials

[0051] The Ca@L prepared in Example 1 R MnCl4·2H2O is a typical example, which emits green light under UV excitation, which is due to the tetrahedral coordination of manganese metal and halogen ions. The optical properties of the crystals are determined by their solid UV-visible diffuse reflectance spectra ( Figure 3 b), Excitation / emission spectra ( Figure 3 c), time-resolved PL spectra ( Figure 3 d), and the radioluminescence spectrum ( Figure 4 ) characterization, the results from Figure 3 It can be seen that Ca@L R MnCl4·2H2O shows good thermal stability. Its UV-visible absorption spectrum is almost consistent with the absorption peak of the excitation spectrum, showing absorption at 250-300nm, 350-400nm, and 400-500nm, but the intensity varies. The sample shows green emission centered at 528nm under UV excitation, which is consistent with the Mn 2+ Ions in Ca@L R The fluorescence decay lifetime of the sample was tested with an excitation wavelength of 375 nm and a measured fluorescence lifetime of 1.91 ms. The fluorescence lifetime of milliseconds is similar to that of other Mn 2+ The compounds that emit light after the ion d→d transition are similar. Figure 4 It can be seen that under X-ray irradiation, the halide Ca@L R The crystal of MnCl4·2H2O emits green light. Its RL spectrum is basically consistent with the emission (PL) spectrum tested by the transient spectrometer, indicating that the final luminescence process of X-ray scintillation luminescence is the same as the PL process.

[0052] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. An X-ray luminescent material, characterized in that: The X-ray luminescent material is a crystalline material, and the chemical formula is Ca@L R MnCl4·2H2O; Among them, L R It is a crown ether ligand.

2. The X-ray luminescent material according to claim 1, characterized in that The crown ether ligand is selected from at least one of the supramolecular entities of the macrocyclic structure represented by formula (1) and formula (2):

3. The method for preparing the X-ray luminescent material according to claim 1 or 2, characterized in that: The steps include: S1. obtaining a crown ether ligand; S2. Dissolving a mixture of crown ether ligands, calcium chloride and manganese chloride in alcohol, and obtaining the X-ray luminescent material after the solvent evaporates.

4. The preparation method according to claim 3, characterized in that: In step S2, the molar ratio of the crown ether ligand, calcium chloride and manganese chloride is 1:(1-2):(1-2); Preferably, the usage ratio of the crown ether ligand to the alcohol is 1 mmol:4-10 mL.

5. The preparation method according to claim 3, characterized in that: In step S2, the conditions for the solvent volatilization include: a temperature of 20 to 40°C and a volatilization time of 10 to 30 minutes.

6. The preparation method according to claim 3, characterized in that: In step S2, the alcohol is selected from at least one of ethanol and methanol.

7. The preparation method according to claim 3, characterized in that: In step S1, the method for preparing the crown ether ligand comprises: A mixture containing the starting material, p-toluenesulfonate raw material and sodium hydroxide is dissolved in 1,4-dioxane, refluxed, filtered and concentrated to obtain a crude product; The crude product was extracted with chloroform / saturated brine to obtain the crown ether ligand.

8. The preparation method according to claim 7, characterized in that: The starting material is selected from at least one of (2R,2R)-2,3-butanediol and R-1,1-bi-2-naphthol; Preferably, the p-toluenesulfonate-based raw material is selected from at least one of triethylene glycol di-p-toluenesulfonate and pentylene glycol di-p-toluenesulfonate; Preferably, the molar ratio of the starting material, the p-toluenesulfonate raw material, and the sodium hydroxide is 1:(0.5-1.5):(2-3); Preferably, the usage ratio of the starting material to 1,4-dioxane is 1 mmol:4-8 mL.

9. The preparation method according to claim 7, characterized in that: The conditions of the reflux reaction include: a reaction temperature of 90 to 110° C. and a reaction time of 48 to 72 hours.

10. Use of the X-ray luminescent material according to claim 1 or 2 or the X-ray luminescent material prepared by the method according to any one of claims 3 to 9 in X-ray detection and imaging technology.

Citation Information

Patent Citations

  • Manganese-based metal organic-inorganic hybrid halide as well as preparation method and application thereof

    CN116478684A